Optimizing Library Donation Book Display: SMART and WASPAS Comparison - Ayunda, Afifah Trista; Atmojo, Wahyu Tisno (Universitas Ibn Khladun Bogor, 2023)
The book display has a significant impact on visitor experience and the efficiency of finding reading materials in the library. In this context, optimizing effective and systematic decisions becomes crucial. This research employs the SMART (Specific, Measurable, Achievable, Relevant, Time-bound) and WASPAS (Weighted Aggregated Sum Product Assessment) approaches in selecting the optimal book display for donations. The SMART method assists in formulating specific criteria and indicators to measure effectiveness, while the WASPAS method utilizes assessment principles based on priority with weighted criteria to consider diverse aspects. The required data for this study includes information about criteria and weighting of the book display. This data will be comprehensively analyzed using both of these approach methods. The accuracy level testing resulted in a value of 99.9917% for the SMART method, which is slightly better than WASPAS with a value of 99.9916%. Based on the above suitability level calculation, the SMART approach is more relevant in this situation to address the issue of recommending donation book displays in the library with the goal of minimizing space and improving book search efficiency.